The Effect of Drill Method Through Handover In Improving Nurses' Ability To Use Personal Protective Equipment (PPE) - Fransisca Renata Arantha E. A; Ni Made Nopita Wati; Desak Made Ari Dwi Jayanti (Healthy-Mu Journal, 2022)
The provision of effective and efficient personal protective equipment (PPE) is very important for health workers who are vulnerable to contracting in treating COVID-19 patients. Drill method is a method of learning by providing repeated skill training. The purpose of this study was to find out the influence of drill method through handover in improving the ability of nurses to use PPE. Types of Pre-Experimental Research with a pre-post test design approach of one group. The number of sample was 13 respondents, the sampling technique used was purposive sampling. Data collection instrument used observation sheet. Data was analysed using the Wilcoxon Signed Ranks Test. The results showed that the average pre-test ability of nurses was mostly 75.95, namely 6 people (45.2%) fall into the category of sufficient, while the average ability of post test was mostly 93.62 which is as many as 13 people (100%) fall into the good category. Wilcoxon Signed Ranks Test analysis results obtained asymp. 0.001, meaning there is an influence of drill method through handover in improving the ability of nurses to use PPE. Drill methods can improve the ability of nurses, especially in using PPE through continuous training in accordance with the stages in the SPO.